Analysis of skill level in flat-water kayaking - Brown, M.; Lauder, M.; Dyson, R. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
Sprint kayaking is a series of complex motions involving the simultaneous activity of balancing the boat, whilst ensuring an efficient maximal force transition is attained through the paddle to the water (Kemecsey and Lauder, 1998). Much investigation has focused on the technique and performance of elite level competitors (Ariel, 1977; Sanders and Baker, 1998), however little previous research has compared elite and amateur paddlers in terms of technique. Sanders and Kendal (1992) investigated skill level differences using a performance model centred on average boat velocity. The research identified key factors that differentiated skill level, the most important being stroke rate (P< 0.05), pull time (P= 0.06) and glide time (P< 0.05). Furthermore Sanders and Kendal (1992) established differences between elite and novice paddlers relating to the path of the paddle for 5 subjects. Due to the limited number of participants, it was the aim of the present research to establish the key technique differences between International, National and Club Kayakers. One hundred and thirty five male and female international (n=78), national (n=38) and club (n=19) level paddlers participating in 200m and 500m competitive events were recorded onto videotape. The extent of spatial movement was rated for each paddler on a 0-5 scale for 22 spatial variables and 7 temporal variables. Statistical analysis was carried out using a one-way ANOVA followed by a Tukey post hoc test and a Kruskal-Wallis test. In addition to the expected significant difference in race times significant differences (P<0.05) were exhibited between the 500m male elite paddlers and national/club paddlers in the stroke rate (Int. 60.49, Nat. 56.29, Club. 50.23 strokes per minute), stroke time (Int. 0.99s, Nat. 1.07s, Club. 1.2s), and pull time (Int. 0.56s, Nat. 0.61s, Club. 0.63s). In addition to differences in temporal variables, significant differences were also found for boat motion, rocking, trunk rotation, leg motion, stroke width, forward reach, leg extension and knee proximity. The results indicate that elite level sprint kayaking technique is characterised by little or no boat motion, a wide stroke and extended forward reach, with high levels of trunk rotation and leg motion indicating a significant contribution of the large muscles of the legs and trunk to performance.